Pelatihan Pencegahan Dan Pertolongan Pertama Cedera Olahraga Bagi Pelatih PPLP Sumatera Barat - Zulman Zulman; Syamsuar Abbas; Deswandi Deswandi (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2019)
The risk of injury can occur in all types of sports and is often experienced by athletes. Sports Injury is an injury to the muscular and skeletal system caused by sports activities. First Aid is emergency assistance to accident victims (sick) quickly and precisely at the scene before being evacuated to an expert person. In general, the management of sports injuries uses the principle of RICE (Rest, Ice, Compression, Elevation) which is always applied at the beginning of the injury before further handling. Exercising excessively and ignoring the correct rules of exercise, even bring injury that endangers himself. This wrong activity is due to heating does not meet the requirements, excessive fatigue, especially in the muscles, and wrong in doing sports movements. The most common injury cases, usually too ambitious to complete training targets or want to improve the training phase. A good coach will always pay attention to the state of the athlete from all aspects, one of which is from the physical state of the athlete. This means that the trainer knows how to manage the athlete not to get injured, and if he has an injury quickly know how to help, especially for minor injuries. However, not all coaches understand how the injury and how it helps for athletes. That is why there is a need for training in sports injuries and how to help for coaches who are expected to be used by athletes.